SCN10A/Nav1.8 modulation of peak and late sodium currents in patients with early onset atrial fibrillation. (22nd July 2014) - Savio-Galimberti, Eleonora; Weeke, Peter; Muhammad, Raafia; Blair, Marcia; Ansari, Sami; Short, Laura; Atack, Thomas C.; Kor, Kaylen; Vanoye, Carlos G.; Olesen, Morten Salling; LuCamp,; Yang, Tao; et al.
Abstract: Aims: To test the hypothesis that vulnerability to atrial fibrillation (AF) is associated with rare coding sequence variation in the SCN10A gene, which encodes the voltage-gated sodium channel isoform NaV 1.8 found primarily in peripheral nerves and to identify potentially disease-related mechanisms in high-priority rare variants using in-vitro electrophysiology. Methods and results: We re-sequenced SCN10A in 274 patients with early onset AF from the Vanderbilt AF Registry to identify rare coding variants. Engineered variants were transiently expressed in ND7/23 cells and whole-cell voltage clamp experiments were conducted to elucidate their functional properties. Resequencing SCN10A identified 18 heterozygous rare coding variants (minor allele frequency ≤1%) in 18 (6.6%) AF probands. Four probands were carriers of two rare variants each and 14 were carriers of one coding variant. Based on evidence of co-segregation, initial assessment of functional importance, and presence in ≥1 AF proband, three variants (417delK, A1886V, and the compound variant Y158D-R814H) were selected for functional studies. The 417delK variant displayed near absent current while A1886V and Y158D-R814H exhibited enhanced peak and late ( I Na-L ) sodium currents; both Y158D and R818H individually contributed to this phenotype. Conclusion: Rare SCN10A variants encoding Nav 1.8 were identified in 6.6% of patients with early onset AF. In-vitro electrophysiological studies demonstrated profoundly altered function in 3/3 high-priority variants. Collectively, these data strongly support the hypothesis that rare SCN10A variants may contribute to AF susceptibility.